Persepsi Masyarakat Terhadap Keefektifan Penggunaan Kwhmeter Prabayar di Wilayah Betngandang Sanur Bali - putra, mahadi; Santiari, D. A. S.; Putra M, Tjokorda Bagus (Majalah Ilmiah Teknologi Elektro, 2018)
In an effort to improve the quality of service and overcome problems such as, electricity customers are not disciplined in paying utility bills each month, metering errors made by PLN employees, and electricity theft. Then PT. PLN issued and implemented a pre-paid electricity system. To find out the public perception of the effectiveness of the prepaid product kWhmeter for the community (middle aged customers (45-59th) and elderly (?60th)), this study investigates the use of products in the Br.Betngandang area of ??Sanur, Bali. The design of this paper is descriptive by conducting surveys to people's homes. Based on population of head of household in region Br. Betngandang obtained the number of samples of 74. To know the public perception of the effectiveness of the use of kWhmeter prepaid then the community is given a questionnaire with 11 statements and 4 questions to be filled. The results in this paper are in the range of 60% - 80% indicating that the use of prepaid kWhmeter products provides a relatively strong effectiveness and this makes a good public perception of prepaid kWhmeter products.